Negative modulation of the GABAAρ1 receptor function by l-cysteine - Beltrán González, Andrea Natalia (2018)
l-Cysteine is an endogenous sulfur-containing amino acid with multiple and varied roles in the central nervous system, including neuroprotection and the maintenance of the redox balance. However, it was also suggested as an excitotoxic agent implicated in the pathogenesis of neurological disorders such as Parkinson′s and Alzheimer′s disease. l-Cysteine can modulate the activity of ionic channels, including voltage-gated calcium channels and glutamatergic NMDA receptors, whereas its effects on GABAergic neurotransmission had not been studied before. In the present work, we analyzed the effects of l-cysteine on responses mediated by homomeric GABAAρ1 receptors, which are known for mediating tonic γ-aminobutyric acid (GABA) responses in retinal neurons. GABAAρ1 receptors were expressed in Xenopus laevis oocytes and GABA-evoked chloride currents recorded by two-electrode voltage-clamp in the presence or absence of l-cysteine. l-Cysteine antagonized GABAAρ1 receptor-mediated responses; inhibition was dose-dependent, reversible, voltage independent, and susceptible to GABA concentration. Concentration-response curves for GABA were shifted to the right in the presence of l-cysteine without a substantial change in the maximal response. l-Cysteine inhibition was insensitive to chemical protection of the sulfhydryl groups of the ρ1 subunits by the irreversible alkylating agent N-ethyl maleimide. Our results suggest that redox modulation is not involved during l-cysteine actions and that l-cysteine might be acting as a competitive antagonist of the GABAAρ1 receptors. (Figure presented.).